TECTONIC MOVEMENTS AND THERMAL EVOLUTION OF THE LITHOSPHERE - Levi K.G.; Lysak S.V. (My University, 1986)
Whether the tectonosphere is active or passive depends on the thermal regime of the Earth's interior and the depth of the lithosphere-astenosphere boundary. Lithospheric thickness increases as it cools and decreases as it warms up. The thermal stability of the lithosphere is regulated by its age and the density of terrestrial heat flow. As the interior temperatures and density of the heat flow increase, the lithosphere thins due to a decrease in the viscosity of its lower horizons that is caused by their partial enrichment in mantle fluids. Thinning of the lower (mantle) part of the lithosphere with a relatively constant crustal thickness results in active vertical movements on the Earth's surface.Astenospheric thickness increases with the growth of interior temperatures and inflow of light differentiates. Under the action of gravity, the lithosphere slides off the astenospheric upwarps, and the mechanical energy released is transformed into heat. Sliding causes additional decrease in the viscosity along the lithosphere-astenosphere boundary, contributes to the growth of the velocity of horizontal movements and of heat flow. The contribution of vertical movements to heat flow may be significant if we take into account that horizontal inhomogeneities of the lithosphere slide one against the other at higher levels, and this is probably responsible for different intralithospheric wave guides.Thus, the thermal evolution of the lithosphere can be one of the major mechanisms of tectonic processes.